Analysis of Competition Fronting the Popularity of Content in Social Networks - Hamid Garmani; Mohamed El Amrani; Mohamed Baslam; Rachid El Ayachi (International Journal of Informatics and Communication Technology (IJ-ICT), 2017)
In the telecommunications domain they are several providers, but customers seeking those that there are good services. In this paper, a study is seeking on two types of providers: content providers CPs and Internet Service Providers ISPs. In this study, we analyzed the impact of Selfishness of Content Providers and Internet Service Providers on their strategies of Price and QoS on their decision strategies. Yet, we formulate our problem as a non-cooperative game among multiple CPs, multiple ISPs competing for the same market. We prove through a detailed analysis uniqueness of pure Nash Equilibrium (NE). Furthermore, a fully distributed algorithm to converge to the NE point is presented. In order to quantify how efficient is the NE point, a detailed analysis of the Price of Anarchy (PoA) is adopted to ensure the performance of the system at equilibrium. Finally, we provide an extensive numerical study to point out the importance of QoS and credibility in the market and the in-fluence of the existing economic relationship between content providers and Internet service providers.